Evolution of a sensory cluster on the legs of Opiliones (Arachnida) informs multi-level phylogenetic relationships. Issue 1 (16th April 2019) - Gainett, Guilherme; Sharma, Prashant P; Fernandes, Nathália; Pinto-Da-Rocha, Ricardo; Giribet, Gonzalo; Willemart, Rodrigo Hirata
Abstract: Phylogenetic relationships in Opiliones (Arachnida) at the suborder level have greatly stabilized in recent years, largely due to advances in molecular systematics. Nonetheless, identifying morphological characters in the context of well-resolved phylogenies is essential for testing new systematic hypotheses and establishing diagnostic markers. Here, we investigate with SEM a promising character system across Opiliones: the sensilla on the distalmost article of legs I and II. We identified four discrete characters and scored species of nearly all families of Laniatores (28 families, 44 species), three Dyspnoi, two Eupnoi and two Cyphophthalmi. Using a phylogenetic backbone compiled from recent and ongoing phylogenomic studies, we trace the evolution of these sensilla using ancestral state reconstruction. We discover a widespread occurrence of three sensilla (a pair of sensilla basiconica and one hooded sensillum) on the anterior legs of all families of Laniatores studied, and that comparable structures occur in the other suborders of Opiliones. Our analysis shows that this sensory field provides diagnostic information at different levels of phylogenetic relationships. We discuss the implications of the widespread occurrence of these sensilla in Opiliones, which have recently been hypothesized as hygro-/thermoreceptors and their putative homology with tarsal organs in Arachnida.